0818 Actigraphy Sleep Assessment In Early Infancy: Associations With Socioeconomic Factors Over Ages One To Six Months. (12th April 2019) - Yu, Xinting; Rueschman, Michael; Kaplan, Emily R; Quante, Mirja; Horan, Christine; Davison, Kirsten; Taveras, Elsie M; Redline, Susan S
Abstract: Introduction: Maturation of sleep/wake patterns across early childhood is linked with brain and physical development. An improved understanding of factors associated with sleep/wake development during early infancy may help elucidate the origins of chronic diseases and provide insight into normative sleep patterns. Actigraphy is a popular objective sleep assessment method due to its ease of data collection in natural home environments, but has not been widely used in infants. The aim of this analysis was to characterize sleep/wake patterns using actigraphy and evaluate the association of demographic/socioeconomic factors with changes in 24-hour and nocturnal sleep duration between one and six months of age. Methods: As part of the ongoing Rise & SHINE (Sleep Health in Infancy & Early Childhood) study, a Massachusetts-based birth cohort that examines sleep patterns and growth in early life, full-term healthy singletons wore an actigraph on their ankle for 3-7 days at approximately one month and six months of age. At each visit, the parents completed concurrent sleep diaries and a subset of questions from the Brief Infant Sleep Questionnaire. Outcomes were changes in nocturnal sleep (7pm-8am) between six and one month of age. Results: The sample includes the first 181 infants (20 Black, 30 Asian, 77 White, 52 Hispanic, 2 multi-racial/other). Of these 44(24%) were offspring of mothers with less than Bachelor degree education and 69(38%) were from households with low income. Nocturnal sleep duration increased from 444.6(95%CI: 433.8, 455.3) to 512.0(95%CI: 501.5, 522.5) minutes between ages one and six months (P<0.001). Increase in nocturnal sleep duration was 67.3 minutes less in infants with low maternal education (16.5±97.6 vs. 83.8±89.4, P<0.001), and 45.3 minutes less in infants with low family household income (39.4±100.0 vs. 84.7±89.0, P=0.002). Conclusion: Actigraphy estimated an average increase of 67.4 minutes of nocturnal sleep from one to six months of age. However, sleep duration, potentially reflecting decreased nocturnal sleep consolidation, increased less over six months in infants from low socioeconomic households, suggesting that early environmental factors may impact sleep neurodevelopment. Support (If Any): NIDDK fund (R01 DK107972)